Archival knowledge: Conceptual frameworks for recent terminology in the KO domain - Tognoli, Natália Bolfarini; Rodrigues, Ana Célia; Chaves Guimarães, José Augusto [UNESP] (IMR Press, 2019)
Despite having the principle of provenance as its guiding element, the archival knowledge organization still prescinds, for conceptual purposes, of greater clarity of its object—the archival knowledge—a fundamental aspect for the sedimentation of the archival studies and of its discursive community in the scope of KO. This article aims to define a conceptual framework to archival knowledge by using Dahlberg's concept theory. In this vein, it established the nominal concept or definiendum—archival knowledge—seeking to analyze its real definition, composed by three inseparable definiens: the concept of finds, the knowledge of documentary form and the knowledge of document creation context. At the end, it demonstrates that archival knowledge can be defined as being a reunion of three indivisible facets in which the archival bond will be contemplated.
Keywords: Archival; Concept; Context; Documents; Knowledge